A review on Knowledge Audit process and tools - Abdul Latif A.S.; Mohd Drus S.; Mohd Shariff S.S. (International Information Institute Ltd., 2023)
Most of the literatures agree that knowledge is one of the important assets of an organization in the current business environment. An effective Knowledge Management (KM) helps organization to leverage on their organizational knowledge resources. This could be attained by conducting a Knowledge Audit (KA) prior to any KM implementation. KA evaluates an organization's knowledge environment by investigating the existence of knowledge and how it will affect the business process. KA will also help an organization to identify its knowledge inventory, knowledge flow and the knowledge owner. A comprehensive KA process supplemented with effective tools would be beneficial to the organization as it will ensure a proper assessment of the current knowledge condition of an organization is attained. However, currently there is no universally accepted KA model that could be directly applied to different organizational structure and environment, as well as lack of descriptive explanation on tools used in every KA activity. This paper presents a comparison analysis of the existing KA models in the literatures. The existing KA models are assessed based on the activities and tools that are being employed. This helps in identification of the suitable tools to be used in each process of KA. 2016 International Information Institute.